(untitled) (Tempo e Argumento, 2021)
The amount of approaches about the São Paulo’s 1932 uprising is not very restrict. Surprisingly, however, the violence that took place in this conflict stood far from the spotlights. More than that. It was supplanted by a softened read of the insurrection, which displays the images of war mobilization and, simultaneously, conceals the bodies’ suffering. This article, consequently, using the profiles of dead combatants killed on the confrontation and the military trials to investigate the war crimes, problematizes the dimensions of the physical violence on the São Paulo’s uprising, its causes and meanings. From this analysis comes up a other side of the rebellion: of brutal and even voluntary aggressions, which, in addition to the “inevitable” circumstances of the war, are rooted in ancient conflicts and hatreds, ingrained among Brazilians at least since the beginning of the republic. Keywords: violence; “Constitutionalist Revolution”; 1932.